Identification and validation of three tumor suppressors associated with the immune response of acute myeloid leukemia - Pan, Yueyuan; Wu, Guocai; Liu, Chenchen; Chen, Minggui; Xia, Tian; Ma, Yonghua; Yang, Zhigang; Wen, Ruiting (Frontiers in Genetics, 2025)
BackgroundAcute myeloid leukemia (AML) is a heterogeneous disorder marked by irregular expansion and maturation, giving rise to the aggregation of immature myeloid precursor cells. Although most patients achieve remission with initial treatment, the majority of relapses lead to poorer overall survival. The bone marrow (BM) immune microenvironment has been proven to significantly affect the progression of AML. However, the mechanisms that cause the imbalance of immune cell subsets and phenotypes remain partially obscure. Therefore, this research sought to explore the immune-regulatory genes and to determine their role in AML.MethodsDifferentially expressed genes (DEGs) were obtained through differential analysis of the AML cohort. Enrichment analyses were applied to explore their biological functions. Weighted Gene Co-expression Network Analysis (WGCNA) was performed to identify the key module of AML. ROC curve analysis was performed to identify hub genes with good predictive power. CIBERSORT and the ESTIMATE algorithm were used to assess the correlation between hub genes and the immune microenvironment of AML. The impact of hub gene expression on the prognosis of AML was verified through prognostic traits and clinical samples.ResultsThrough differential analysis and WGCNA, seven genes were identified as markedly related to the development of AML. By mapping ROC curves, three hub genes were verified: CCR7, SLC16A6, and MS4A1, which have high diagnostic value for AML. Additionally, an imbalanced immune microenvironment was found to be common in AML. Three hub genes were significantly associated with immune components, including immune cells and immunomodulatory factors. Ultimately, through the validation of clinical samples and the analysis of prognostic characteristics, three genes were confirmed to be reduced in AML patients, and their high expression suggested a favorable prognosis.ConclusionOur study identified and validated the efficacy of SLC16A6, CCR7, and MS4A1 as tumor suppressors implicated in AML progression and related to immune cell infiltration.